The vulnerability of the cities of Piura to flooding as a result of the increase in rainfall in El Niño episodes - Chambi Echegaray, Gina (2023)
The cities of Piura have experienced flood disasters throughout their history, mainly related to the El Niño phenomenon. The objective of this research was to develop strategies for good management of urban vulnerability reduction in the cities of Piura. The methodology used is descriptive and the procedure of the present research comprises three phases: information gathering, discussion with related entities, and desk work. The results allowed and will allow determining actions for prevention, reduction, preparation and reconstruction, as well as mitigation and adaptation to climate change.